Cerise C. Jack papers relating to the Sacco and Vanzetti case - Jack, Cerise C.; Sacco-Vanzetti Defense Committee; Sacco-Vanzetti National League
Chiefly letters written by Nicola Sacco, his wife Rose Sacco, and Bartolomeo Vanzetti to Cerise C. Jack and her daughter Betty Wirth during the incarceration of Nicola Sacco and Vanzetti. Includes related correspondence, newletters, pamphlets, and bulletins chiefly of the Sacco-Vanzetti Defense Committee and the Sacco-Vanzetti National League relating to the Sacco-Vanzetti Trial, Dedham, Mass., 1921.
Photocopies, in part.
Friend and supporter of Nicola Sacco and Bartolomeo Vanzetti, immigrant Italian anarchists tried and executed for murder.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Sacco, Nicola, -- 1891-1927 -- Correspondence; Sacco, Rose -- Correspondence; Vanzetti, Bartolomeo, -- 1888-1927 -- Correspondence; Wirth, Betty -- Correspondence; Sacco-Vanzetti Trial, Dedham, Mass., 1921.; Trials (Murder) -- Massachusetts